Are concentrations of clusterin and beta-2-glycoprotein I dysregulated in HIV associated preeclampsia?. (August 2020) - Mlambo, Zinhle P.; Varaden, Deneshree; Moodley, Jagidesa; Naicker, Thajasvarie
Abstract: Objective: To evaluate the levels of serum beta-2-glycoprotein I (β2 GP1) and clusterin in the duality of Pre-eclampsia and HIV. Method: Stored serum samples collected from 72 pregnant women were stratified according to the pregnancy type (pre-eclamptic and healthy normotensive groups) and HIV status (positive or negative). A Bio-Plex multiplex immunoassay was used to determine the concentrations of clusterin and β2 GP1. Results: Clusterin concentrations differed significantly ( p = 0.01) between the HIV positive (+) (mean = 123 800 ng/ml; 95 % CI: 105 400-142 200) vs. HIV negative (-) (mean = 92 190 ng /ml; 95 %CI: 75 840-108 500) groups and across all groups ( p = 0.0006). Beta-2-glycoprotein I concentration differed significantly based on HIV status ( p < 0.0001); HIV+ (mean = 393 649 ng/ml; 95 %CI: 30 300–467 000) vs HIV- (mean = 224 309 ng/ml; 95 %CI: 154 000–294 700) and across all groups ( p < 0.0001). No significant difference was observed between normotensive and Pre-eclamptic groups for both clusterin and β2 GPI. Conclusion: Serum concentrations of clusterin and β2 GPI were significantly increased in HIV positive pregnancies. It is postulated that both clusterin and β2 GPI may have a role in HIV disease progression. These findings need to be confirmed in studies having larger sample sizes and detailed information on anti-retroviral therapy.